Catering Business Management Practice and Entrepreneurial Motivation among Culinary Arts Students at State Vocational High Schools in the Special Region of Yogyakarta - Nisa, Armalita Sinta; Solihin, Solihin (Journal of Engineering and Vocational Education, 2026)
Purpose of the study: This study aims to examine the effect of learning practices in culinary service business management on students’ entrepreneurial motivation in the Culinary Expertise Program at State Vocational High Schools in the Special Region of Yogyakarta.Methodology: This study used a quantitative correlational research design. Data were collected through observation sheets of culinary service business management practices and questionnaires measuring entrepreneurial motivation. The sample consisted of 228 students. Data were analyzed using descriptive statistics, Pearson correlation analysis, and simple linear regression with SPSS version 16.Main Findings: The results showed that the learning practice of culinary service business management had a significant relationship with students’ entrepreneurial motivation. The correlation coefficient was 0.216, which was higher than the r-table value of 0.113 at a 5% significance level. The regression equation obtained was Y = 73.134 + 1.223X with a contribution of 4.7%.Novelty/Originality of this study: This study highlights the role of practical culinary business management learning as a contributing factor in strengthening entrepreneurial motivation among vocational students. The integration of observation-based practice data and motivational survey analysis provides empirical evidence of how practical entrepreneurship learning influences students’ entrepreneurial attitudes in vocational education.